Notes and News - Tracey, Hugh (International Library of African Music, 1962)
Talking-Gongs and Independence Day in Congo - Ethnomusicology in Britain - International Folk Music Council - Church Music Workshop conducted by Robert Kauffman from Old Umtali Methodist Mission, Southern Rhodesia - International Congress of African Culture, Salisbury, Southern Rhodesia, August 1962 -
Keywords: African Music; Southern Rhodesia; Talking-gongs; Republic of the Congo (Léopoldville)